Cover Feature: Synthesis of 2‐Substituted 1, 2, 3‐Triazoles via an Intramolecular N–N Bond Formation (Eur. J. Org. Chem. 5/2020). Issue 5 (23rd January 2020) - Chen, Cheng‐yi; Lu, Xiaowei; Holland, Mareike C.; Lv, Shichang; Ji, Xuebao; Liu, Wei; Liu, Jie; Depre, Dominique; Westerduin, Pieter
Abstract : The Cover Feature shows how the in‐situ generated hydrazonium species leads to the formation of a wide variety of 2‐aryl‐1, 2, 3‐triazoles under very mild conditions. A preliminary computational DFT study on the reaction pathway suggest that the reaction likely follows an intramolecular S N 2 displacement mechanism with the trimethyl‐ammonium moiety serving as a good leaving group for the intramolecular N‐N bond formation. More information can be found in the Communication by C.‐y. Chen et al.